Pengaruh Kualitas Pelayanan, Fasilitas Pelayanan, Disiplin Kerja dan Kompetensi Pegawai terhadap Kepuasan Masyarakat di Kelurahan Leteh Rembang - Aisha Rahma Lathifa Zafira; Dian Ayu Liana Dewi (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the influence of Service Quality, Service Facilities, Work Discipline, and Employee Competence on Community Satisfaction in Leteh Urban Village, Rembang. The approach used is quantitative, employing multiple linear regression analysis to measure the relationship between these variables. The research involved the community population of Leteh Urban Village with a sample of 100 respondents. The research findings indicate that the relationship between Service Quality and Service Facilities on Community Satisfaction is positive but not statistically significant. Meanwhile, the relationship between Work Discipline and Employee Competence on Community Satisfaction is positive and statistically significant. Therefore, increasing community satisfaction needs to be carried out through strategic steps, such as: tightening Service SOPs, conducting intensive training so that all staff provide uniformly excellent service, and introducing a touch of personalization. Furthermore, efforts should include increasing routine maintenance and cleanliness so that all facilities function optimally, and adding truly relevant and modern features, such as accelerating digitalization (e.g., digital queuing systems or fast Wi-Fi). These efforts are expected to foster a harmonious working relationship among the community members, thereby supporting and enhancing overall community satisfaction.